Rasionalisme Mu’tazilah dan Pengaruhnya Analisis Historis - Heru Chakra Setiawan; Afif Gita Fauzi (AL-MUFASSIR, 2022)
This study discusses the character of rational Mu'tazilite thought and its influence in the journey of Islam. This research is qualitative by using the method of documentary data analysis. As for the results of his research that their thinking was much influenced by Greek philosophy. So the Mu'tazilah are often referred to as Islamic rationalists. The Mu'tazila rational style became a smooth way for discussion and development of thought and science that brought progress to Islamic civilization at that time